PLEVRANIN SOLİTER FİBRÖZ TÜMÖRÜ İLE İZLEDİĞİMİZ 3 OLGU - AKI, Hilal; DURAK, Haydar; KAYNAK, Kamil; DEMİRHAN, Özkan and ÖZ, Büge (Cerrahpaşa Medical Journal, 2014)
Background.- Solitary fibrous tumors of the pleura are very rare neoplasms. The majority of these tumors is benign, but about 10-20% fulfills the criteria of malignancy. Clinical presentation varies according to the size and intrathorasic localization. In early stages, though the tumors may gradually grow to enourmous size and then cause symptoms such as cough, chest pain and dyspnea, also paraneoplastic syndromes such as hypoglisemia or digital clubbing. Histologically, they are characterized by fibroblast-like cells and connective tissue in varying proportions. The majority of solitary fibrous tumors are immunoreactive for CD34. Surgical resection is usually curative. Observation.- We reported three cases with solitary fibrous tumor of pleura. Their clinical, radiologic, histologic and immunhistochemical features were emphasized with a review of related current knowledge.